Sustained Effects of Acupuncture Stimulation Investigated with Centrality Mapping Analysis - Long, Xiangyu; Huang, Wenjing; Napadow, Vitaly; Liang, Fanrong; Pleger, Burkhard; Villringer, Arno; Witt, Claudia M.; Nierhaus, Till; Pach, Daniel (Frontiers in Human Neuroscience, 2016)
Acupuncture can have instant and sustained effects, however its mechanisms of action are still unclear. Here we investigated the sustained effect of acupuncture by evaluating centrality changes in resting-state functional magnetic resonance imaging after manually stimulating the acupuncture point ST36 at the lower leg or two control point locations (CP1 same dermatome, CP2 different dermatome). Data from a previously published experiment evaluating instant BOLD effects and S2-seed-based resting state connectivity was re-analyzed using eigenvector centrality mapping (ECM) and degree centrality mapping (DCM). These data-driven methods might add new insights into sustained acupuncture effects on both global and local inter-region connectivity (centrality) by evaluating the summary of connections of every voxel. We found higher centrality in parahippocampal gyrus and middle temporal gyrus after ST36 stimulation in comparison to the two control points. These regions are positively correlated to major hubs of the default mode network, which might be the primary network affected by chronic pain. The stronger integration of both regions within the whole-brain connectome after stimulation of ST36 might be a potential contributor to pain modulation by acupuncture. These findings highlight centrality mapping as a valuable analysis for future imaging studies investigating clinically-relevant outcomes associated with physiological response to acupuncture stimulation.